The stem cell factor/c-kit receptor pathway enhances proliferation and invasion of pancreatic cancer cells - Okada Yuji; Sato Mikinori; Funahashi Hitoshi; Matsuo Yoichi; Ochi Nobuo; Takahashi Hiroki; Sawai Hirozumi; Yasuda Akira; Takeyama Hiromitsu; Manabe Tadao (Molecular Cancer, 2006)
Abstract Background The transmembrane protein c-kit is a receptor tyrosine kinase (KIT) and KIT is expressed in solid tumors and hematological malignancies such as gastrointestinal stromal tumor (GIST), small-cell lung cancer and chronic myelogenous leukemia (CML). KIT plays a critical role in cell proliferation and differentiation and represents a logical therapeutic target in GIST and CML. In pancreatic cancer, c-kit expression has been observed by immunohistochemical techniques. In this study, we examined the influence of c-kit expression on proliferation and invasion using five pancreatic cancer cell lines. In addition, the inhibitory effect of imatinib mesylate on stem cell factor (SCF)-induced proliferation and invasion was evaluated. Finally, we also analyzed KIT and SCF expression in pancreatic cancer tissues using immunohistochemistry and correlated the results with clinical features. Results RT-PCR revealed that two pancreatic cancer cell lines, PANC-1 and SW1990, expressed c-kit mRNA. By Western blot analysis, c-kit protein was also present in those lines. In KIT-positive pancreatic cancer cell lines, proliferation and invasion were significantly enhanced by addition of SCF. In contrast, SCF did not enhance proliferation and invasion in the three KIT-negative lines (BxPC-3, Capan-2 and MIA PaCa-2). 5 μM imatinib mesylate significantly inhibited SCF-enhanced proliferation to the same extent compared with the control. Similarly, SCF-enhanced invasive ability was significantly inhibited by 5 μM imatinib mesylate. KIT was expressed in 16 of 42 clinical specimens by immunohistochemistry, and KIT expression was significantly related to venous system invasion. Furthermore, patients expressing both KIT and SCF had a somewhat lower survival. Conclusion Our results demonstrated that the SCF-KIT pathway enhanced the proliferation and invasiveness in KIT-positive pancreatic cancer cell lines and that the enhanced proliferation and invasion were inhibited by imatinib mesylate. We propose that inhibitors of c-kit tyrosine kinase receptor have the potential to slow the progression of KIT-positive pancreatic cancers.